PENGARUH TRADISI DOA DI TAMAN DOA IMATUKA TERHADAP PERKEMBANGAN SPIRITUAL ORANG MUDA KATOLIK DI PAROKI SANTA MARIA LOURDES SUMBER MAGELANG - Yunita, Elaviana; Hartutik, Hartutik; Wijoyoko, Gregorius Daru; Wuriningsih, FR (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2025)
This research aims to analyze the influence of prayer traditions in Imatuka Prayer Garden on the spiritual development of Catholic Youth (OMK) at Santa Maria Lourdes Sumber Parish, Magelang. Using a mixed-method approach with convergent parallel design, the study collected quantitative data from 39 Catholic youth respondents and qualitative data through interviews with five key informants. Quantitative results showed significant positive correlations between prayer frequency and duration (R² = 0.324, p < 0.001), prayer experience intensity (R² = 0.288, p < 0.001), and prayer variety (R² = 0.395, p < 0.001) with youth spiritual development. Qualitative findings revealed that Imatuka Prayer Garden functions as a sacred space that facilitates personal reflection, spiritual connection, and community formation. The prayer garden's conducive environment for silence and connection with nature was highlighted as a key factor enabling deeper spiritual experiences. The research concludes that prayer traditions at Imatuka Prayer Garden significantly contribute to Catholic youth spiritual development in line with the Continuous Formatio of Faith (FIBB) framework of Semarang Archdiocese, particularly in strengthening faith identity, devotional practices, and ecclesial participation.